BIMBINGAN KONSELING KARIR DALAM PENDEKATAN SPRITUAL - SISRA ZENI ZENI (Universitas Islam Negeri Mahmud Yunus Batusangkar, 2013)
Spritual aspect is an important component in starting a work because it correlates with work etiquette itself. This research is aimed to describe of how teaching in Islam concept about a work, guidances and councelling carrier, even doing spritual approaching in councelling carrier. Actually, moslem people were very lucky because all guidances have been stated clear. They just translate and apprecite them in daily, weekly, and mothly activities. Whatever and whenever these activies were done, they cannot saparate them from spritual aspect.Kata kunci: konseling, karir, spritual